2004
DOI: 10.1098/rspb.2003.2638
|View full text |Cite
|
Sign up to set email alerts
|

Complex biogeographic history of a Holarctic passerine

Abstract: Our analysis of the ND2 sequences revealed six clades within winter wrens (Troglodytes troglodytes). These clades corresponded to six geographical regions: western Nearctic, eastern Nearctic, eastern Asia, Nepal, Caucasus and Europe, and differed by 3-8.8% of sequence divergence. Differences among regions explained 96% of the sequence variation in winter wren. Differences among individuals within localities explained 3% of the sequence variation, and differences among localities within regions explained 1%. Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 22 publications
8
98
0
Order By: Relevance
“…Typically, such species are divided into one or more different subspecies on each continent, based primarily on morphology (del Hoyo et al 1992(del Hoyo et al -2008. Recent studies of genetic divergence in a few Holarctic species have found relatively high levels of divergence between Palearctic and Nearctic populations (e.g., Drovetski et al 2004;Koopman et al 2005;Zink et al 2006). To date, no comprehensive study of the genetic divergence between populations on each side of the Atlantic Ocean has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, such species are divided into one or more different subspecies on each continent, based primarily on morphology (del Hoyo et al 1992(del Hoyo et al -2008. Recent studies of genetic divergence in a few Holarctic species have found relatively high levels of divergence between Palearctic and Nearctic populations (e.g., Drovetski et al 2004;Koopman et al 2005;Zink et al 2006). To date, no comprehensive study of the genetic divergence between populations on each side of the Atlantic Ocean has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Sight reports (Kroodsma 1980, Hejl et al 2002 and mitochondrial DNA (Drovetski et al 2004). Formerly considered conspecific with T. hiemalis but separated on the basis of the absence of free interbreeding and maintenance of genetic integrity in their contact zone (Toews and Irwin 2008).…”
Section: Caprimulgus Vociferus Arizonaementioning
confidence: 99%
“…The Pacific Wren was recently split from the Winter Wren (Troglodytes hiemalis) based on song, genetic structure, and reproductive isolation in areas of sympatry (Toews and Irwin 2008); the species was also split from the Eurasian Wren (Troglodytes troglodytes) in Europe and Asia, primarily due to differences in genetic structure (Drovetski et al 2004, Chesser et al 2010). However, a detailed within-species assessment of the population genetics of Pacific Wrens in Alaska is currently insufficient to assess the conservation status of the populations and subspecies occurring there, and the need for additional information has been identified as a priority for future research (Toews and Irwin 2012).…”
Section: Introductionmentioning
confidence: 99%